IESDAD :improved energy efficient structure- free data aggregation and delivery protocol in WSN - Kaur, Avneet; Sharma, Neeraj (International Journal of Engineering and Technology, 2018)
The wireless sensor is deployed to sense large amount of data from the far places. With the large deployment of the sensor networks, it faces major issues like energy consumption, dynamic routing and security. The Energy efficient structure-free data aggregation and delivery (ESDAD) is the protocol which is hierarchal in nature. The ESDAD protocol can be further improved to increase lifetime of wireless sensor networks. The base station localizes the position of each sensor node and defines level of each node for the data transmission. In the ESDAD protocol, the next hop node is selected based on cost function for the data transmission. In this research work, improved in ESDAD protocol is proposed in which gateway nodes are deployed after each level for the data transmission. The sensor node will sense the information and transmit it to gateway node. The gateway node aggregates data to the base station and simulation results show that improved ESDAD protocol performs well in terms of energy consumption and number of throughput.Â